Availability of competencies among teachers of gifted, talented and creative students in governmental schools in The State of Palestine - Mustafa, Wafa' Subhi (Journal of Educational and Psychological Sciences, 2023)
This study aimed to develop list of competencies among teachers of gifted, creative and gifted students in the State of Palestine. The researcher relied on international standards to develop these lists of competencies and controls. The tool consisted of five lists: cognitive, educational, social, functional and developmental competencies. To achieve the objectives of the study, the descriptive analytical approach was followed. The study tool was applied to a random sample of (557) male and female teachers working at public schools from Nablus, Jenin and Tulkarm. The results of this study showed that the study tool possess a high degree of validity and reliability The results of this study indicated that functional competencies are the most available, followed by social, cognitive and developmental competencies. Educational competencies are the least present. It was also found that there are statistically significant differences in cognitive, educational, social and developmental competencies in favor of male teachers. These differences are attributed to the gender variable. However, there were no differences in functional competencies. There are also no statistically significant differences due to academic qualification, years of experience and educational level. There are also no differences in the cognitive, educational, social and developmental competencies that can be attributed to the directorates of education. However, there are statistical differences in functional competencies, and the differences were in favor of teachers in Jenin and teachers in Tulkarm compared to teachers in southern Nablus. In light of the results, the study recommended the necessity of adopting competency control lists for gifted and creative teachers and their teachers, as this tool is an indicator of performance and adequacy in the sense that it helps in recruitment, training, qualification and evaluation.